IMPACT OF GUT MICROBIOTA ON POSTOPERATIVE RECOVERY AND WOUND HEALING: NEW INSIGHTS AND EMERGING THERAPIES - Pedro do Valle Varela, João; Pedro de Morais Siqueira, João; Silva Campos, Fernando; Marques de Araújo Fernandes, Graziella; Volponi Pessoti, Hugo; Julia Milholo Robles, Ana (Health and Society, 2024)
The gut microbiota, made up of trillions of microorganisms that inhabit the gastrointestinal tract, plays a fundamental role in human health, influencing immunological and metabolic processes and even wound healing. Recently, studies have shown that the gut microbiota can also significantly impact post-operative recovery. This emerging field of research is revealing new insights into how the composition and function of the microbiota can affect the recovery of patients after surgery and the effectiveness of wound healing. Understanding these interactions paves the way for the development of innovative therapies that can improve surgical outcomes and promote faster and more efficient recovery. This review seeks to explore the new insights into the impact of gut microbiota on postoperative recovery and wound healing, highlighting the emerging therapies and scientific advances that are shaping this field. By investigating the current literature and evaluating recent clinical studies, we aim to provide a comprehensive overview of the interactions between the microbiota and healing processes, as well as discussing the therapeutic implications of these findings for clinical practice. This literature review aims to investigate the relationship between the gut microbiota and various aspects of health and disease, using a selected set of landmark studies. To this end, high-impact publications were selected that address topics related to the gut microbiota, its functions, benefits and implications for human health. Post-operative recovery and wound healing are complex processes that involve a series of biological responses, including inflammation, tissue remodeling and cell regeneration. The gut microbiota influences these processes in a number of ways, starting with the modulation of the immune system. Studies have shown that a healthy microbiota can promote a balanced inflammatory response, which is crucial for proper wound healing and surgical recovery. Imbalances in the microbiota, known as dysbiosis, can lead to exacerbated or insufficient inflammatory responses, impairing healing and increasing the risk of post-operative complications. The two-way communication between the gut and other organs, known as the gut-organ axis, is fundamental to understanding how the gut microbiota can influence post-operative recovery. Metabolites produced by the microbiota, such as short-chain fatty acids (SCFA), have anti-inflammatory and immunomodulatory effects that can favor wound healing. In addition, the intestinal microbiota can influence the integrity of the intestinal barrier, preventing bacterial translocation and consequent systemic infection, a common complication after surgery. Based on these insights, several emerging therapies are being developed to modulate the gut microbiota and improve post-operative outcomes. One of the promising approaches is the use of probiotics and prebiotics. Probiotics are live microorganisms that, when administered in adequate amounts, confer health benefits on the host, while prebiotics are substrates that promote the growth and activity of beneficial bacteria in the gut. Clinical studies have shown that supplementation with specific probiotics can reduce the incidence of post-operative infections and improve wound healing. Another innovative approach is fecal microbiota transplantation (FMT), which involves transferring microbiota from a healthy donor to a patient with dysbiosis. FMT has shown promising results in restoring the intestinal microbiota and improving post-operative outcomes in patients undergoing major surgery. In addition, diet and nutrition play a crucial role in modulating the microbiota. Diets rich in fiber and bioactive compounds, such as polyphenols, can promote a healthy microbiota and consequently improve postoperative recovery and wound healing. It is concluded that the impact of gut microbiota on postoperative recovery and wound healing is a rapidly evolving field of research with significant potential to transform clinical practices. New insights are revealing how the microbiota influences inflammatory and immunological processes essential for surgical recovery. Emerging therapies, such as probiotics, prebiotics and fecal microbiota transplantation, are showing promising results in improving postoperative outcomes. Modulation of the gut microbiota represents an innovative and effective approach to optimizing patient recovery and promoting faster and more efficient healing. With further research and the integration of this knowledge into clinical practice, it is hoped that microbiota intestinal becomes a key component in post-operative management and wound care, significantly improving patients’ quality of life.